2020
DOI: 10.1016/j.jtho.2019.12.126
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib for the Treatment of NSCLC Harboring Uncommon EGFR Mutations: A Database of 693 Cases

Abstract: Introduction: Limited clinical data are available regarding the efficacy of EGFR tyrosine kinase inhibitors (EGFR TKIs) in patients with NSCLC harboring uncommon EGFR mutations. This pooled analysis assessed the activity of afatinib in 693 patients with tumors harboring uncommon EGFR mutations treated in randomized clinical trials, compassionate-use and expanded-access programs, phase IIIb trials, noninterventional trials, and case series or studies. Methods: Patients had uncommon EGFR mutations, which were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
204
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(227 citation statements)
references
References 76 publications
21
204
1
1
Order By: Relevance
“…However, the impact of this discrepancy on patient care is very low, as efficient and approved therapies are missing for those mutations [20,21]. Thus, these very rare mutations were not reported to be actionable for the different TKIs [22][23][24]. It is important to be aware of the possibility of obtaining a false-negative EGFR mutation using the Idylla device, however, only one discrepancy on druggable alterations was observed, highlighting the reliability of the Idylla device [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of this discrepancy on patient care is very low, as efficient and approved therapies are missing for those mutations [20,21]. Thus, these very rare mutations were not reported to be actionable for the different TKIs [22][23][24]. It is important to be aware of the possibility of obtaining a false-negative EGFR mutation using the Idylla device, however, only one discrepancy on druggable alterations was observed, highlighting the reliability of the Idylla device [25].…”
Section: Discussionmentioning
confidence: 99%
“…The median OS was 19.4 months (95% CI: 16.4–26.9) [ 13 ]. In a recent afatinib study ( n = 315), it showed activity against major uncommon mutations (median TTF, 10.8 months; 95% CI: 8.1–16.6; ORR, 60.0%), compound mutations (median TTF, 14.7 months; 95% CI: 6.8–18.5; ORR, 77.1%), other uncommon mutations (median TTF, 4.5 months; 95% CI: 2.9–9.7; ORR, 65.2%), and some exon 20 insertions (median TTF, 4.2 months; 95% CI: 2.8–5.3; ORR, 24.3%) in EGFR -TKI naïve patients [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uncommon EGFR mutations account for 7–23% of EGFR mutation-positive NSCLCs. Uncommon EGFR mutations can be categorized as follows: (i) de novo T790M; (ii) exon 20 insertions; (iii) “major” uncommon mutations Gly719Xaa (G719X), Leu861Gln (L861Q), and Ser768Ile (S768I); (iv) compound mutations; (v) other uncommon mutations [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Afatinib shows potent activity against wild-type and mutant forms of EGFR (53)(54)(55)(56). However, patients who initially benefit from EGFR-targeted therapies eventually develop resistance (19).…”
Section: Discussionmentioning
confidence: 99%